2021
DOI: 10.3389/fcell.2020.594283
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 Attenuates Cortical Astrocytic Apoptosis and Inflammation in Cerebral Ischemic/Reperfusion Injury

Abstract: Transient receptor potential canonical 6 (TRPC6) channel is an important non-selective cation channel with a variety of physiological roles in the central nervous system. Evidence has shown that TRPC6 is involved in the process of experimental stroke; however, the underlying mechanisms remain unclear. In the present study, the role of astrocytic TRPC6 was investigated in an oxygen–glucose deprivation cell model and middle cerebral artery occlusion (MCAO) mouse model of stroke. HYP9 (a selective TRPC6 agonist) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In addition, TRPC6 is involved in immune responses regulating transendothelial migration, chemotaxis, phagocytosis, and cytokine release 19 , 20 . A recent study using pharmacological blockage of TRPC6 in mice demonstrated that decreased Ca 2+ entry due to TRPC6 contributed to reducing astrocytic apoptosis, cytotoxicity and inflammatory responses in cerebral ischemic/reperfusion insult 30 . Given that, in the present study we hypothesized that TRPC6 inhibition may also exhibit nephroprotective effects in AKI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TRPC6 is involved in immune responses regulating transendothelial migration, chemotaxis, phagocytosis, and cytokine release 19 , 20 . A recent study using pharmacological blockage of TRPC6 in mice demonstrated that decreased Ca 2+ entry due to TRPC6 contributed to reducing astrocytic apoptosis, cytotoxicity and inflammatory responses in cerebral ischemic/reperfusion insult 30 . Given that, in the present study we hypothesized that TRPC6 inhibition may also exhibit nephroprotective effects in AKI.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the mechanisms to maintain the stability of the internal environment ( Carneiro and El-Deiry, 2020 ). Evidence shows that neuronal apoptosis is the basic form of delayed neuronal death after cerebral IR ( Liu et al, 2020 ). Anti-apoptotic Bcl2 and pro-apoptotic Bax were determined to play key roles in cell survival or death ( Pihán et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRP canonical 6 (TRPC6), a non-selective cationic channel expressed in astrocytes with a plethora of functions in the CNS, has been implicated in the pathophysiology of AD and other pathological processes including neuroinflammation and ischemia [ 325 ]. Hyperforin, a TRPC6 agonist, can increase intracellular calcium levels, reduce astrogliosis and disaggregate Aβ aggregates, with effects on spatial memory [ 326 , 327 ].…”
Section: Astrocytes As a Therapeutic Target: Treatment And Neuroprote...mentioning
confidence: 99%